Assaultive trauma, alcohol use, and alcohol‐related consequences among American Indian adolescents. (7th April 2022) - Spillane, Nichea S.; Nalven, Tessa; Goldstein, Silvi C.; Schick, Melissa R.; Kirk‐Provencher, Katelyn T.; Jamil, Aayma; Weiss, Nicole H.
Abstract: Background: American Indian (AI) adolescents report disproportionate higher rates of alcohol use and alcohol‐related consequences than adolescents from other racial/ethnic groups. Trauma exposure is also reported at high rates among AI individuals and likely confers risk for alcohol use. The purpose of the present study was to examine the effects of assaultive trauma experiences (e.g., physical assault, sexual assault) on alcohol use and alcohol‐related consequences in AI adolescents. Methods: We conducted a secondary analysis of self‐reported data on trauma exposure, alcohol consumption, and lifetime alcohol‐related consequences provided by AI 7th to 12th graders residing on or near a reservation (n = 3498, Mage  = 14.8; 49.5% female). Institutional Review Boards, tribal authorities, and school boards approved the study protocols prior to beginning data collection. Results: Nearly half (49.3%, n  = 1498) of AI adolescents reported having experienced at least one assaultive trauma in their lifetime. Those who had experienced assaultive trauma were more likely to report lifetime alcohol use ( χ 2  = 111.84, p  < 0.001) and experienced greater alcohol‐related consequences ( t (1746) = 12.21, p  < 0.001) than those with no assaultive trauma exposure. Multilevel regression analyses indicated that a greater number of assaultive traumatic events was significantly associated with greater odds of lifetime alcohol use ( p  < 0.001, OR = 1.81, 95% CI [1.65, 2.00]) and having experienced a greater number of alcohol‐related consequences ( b  = 0.36, SE = 0.04, t  = 16.95, p  < 0.001, 95% CI [0.31, 0.46]). Conclusions: Findings of the present study highlight the relevance of exposure to assaultive trauma to AI adolescents' use of alcohol and experiences of alcohol‐related consequences. These findings support the need for trauma‐informed interventions in addressing alcohol use among AI adolescents. Abstract : American Indian (AI) adolescents who had experienced assaultive trauma in their lifetime were more likely to report lifetime alcohol use and experienced greater alcohol‐related consequences compared to those with no assaultive trauma exposure. Multilevel regression analyses indicated that a greater number of assaultive traumatic events was significantly associated with greater odds of lifetime alcohol use and having experienced a greater number of alcohol‐related consequences. Findings implicate the need for trauma‐informed interventions in addressing AI adolescent alcohol use.